When nurturing is conditional: how NEET practitioners position the support they give to young people who are not in education, employment or training. Issue 1 (2nd January 2019) - Avila, Tais Brias; Rose, Jo
ABSTRACT: This paper explores the perceptions of professionals working with young people who are NEET (Not in Employment, Education or Training) about their role in young people's trajectories. The issue of professionally and educationally inactive young people is a growing concern in Western economies and has been at the forefront of government agendas for the last 30 years. However, policies designed to re-engage young people position them as lacking in qualities sought by employers. Meanwhile, the educational provision dedicated to NEETs is often described as providing low-value qualifications, and practitioners who work with NEETs are considered to have a lower status than other teaching professionals. A mixed-methods study was conducted including six semi-structured interviews and an online survey completed by 25 professionals working with NEETs. The findings highlight that professionals working with NEETs are positioned in a contradictory role. On the one hand, they are tasked with delivering courses based on educational policies that place the responsibility for employment within the individual. On the other hand, they perceive NEET young people's circumstances as the result of structural inequalities. Practitioners seem to reconcile these contradictions by construing their own role as the provision of a safe space in which young people can develop.